The Role of Accounting Theory in Enhancing Transparency and Accountability in the Management of the Pondok Indah MSME Housing Area, RW 09, Kutabumi Village, Tangerang Regency - Bagas Gilang Ramdhani; Defa Irodat Alam; Sri Wahyuni; Ira Igustiningrum; Suripto Suripto; Baharuddin Saga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute 60.5% to Indonesia's GDP but continue to face significant challenges in financial management, particularly low financial literacy, the absence of standardized bookkeeping, lack of separation between personal and business finances, and minimal utilization of digital technology. This community service program aimed to enhance the understanding of accounting theory's role in improving transparency and accountability in financial management among 25 MSME actors in Perumahan Pondok Indah RW 09, Kelurahan Kutabumi, Kecamatan Pasar Kemis, Kabupaten Tangerang. The implementation method used was problem-based solution training, which included problem identification, solution planning, training and mentoring on simple bookkeeping (recording income, expenses, and profit calculation), introduction and practice of the Buku Warung digital application, evaluation through pre-test and post-test, and program sustainability planning. The outcomes showed a significant increase in participants' average understanding from 12.5% to 75% (a 62.5% improvement), with 85% of participants understanding the importance of financial recording, 80% understanding the separation of personal and business finances, and 60% ready to use the Buku Warung application. This program successfully improved financial literacy, encouraged transparent and accountable financial management, and established sustainable collaboration between the university and local government.